Evaluating the efficacy of metformin in reducing hyperprolactinemia among patients with schizophrenia: A meta-analysis of randomized controlled trials - Goh, Kah Kheng; Chen, Chun-Hsin; Lu, Mong-Liang (Journal of psychopharmacology (Oxford), 2025)
Antipsychotic treatment is commonly associated with hyperprolactinemia, leading to menstrual disturbances, sexual dysfunction, and decreased bone mineral density. Nearly all antipsychotic drugs can elevate prolactin levels, affecting up to 70% of patients with schizophrenia. We aim to evaluate the potential therapeutic role of metformin in reducing hyperprolactinemia among these patients. We systematically searched PubMed, CNKI, Embase, Cochrane, and Web of Science through January 31, 2024, for randomized controlled trials (RCTs) evaluating metformin's effect on prolactin levels in patients with schizophrenia. Data were extracted and synthesized using random-effects meta-analysis. This meta-analysis included 10 RCTs with 1046 participants (584 received metformin and 462 received placebo or no treatment). Metformin significantly reduced prolactin levels compared to control groups (SMD = -0.98, 95% CI: -1.62, -0.35, = 0.002; transformed MD = -34.88 ng/mL, 95% CI: -57.65, -12.46). Subgroup analyses indicated that higher doses (1500 mg), shorter treatment durations (<24 weeks), higher BMI (>25 kg/m²), and longer illness duration (>1 year) were associated with more significant prolactin reductions. Metformin was well tolerated with no significant increase in adverse events or all-cause discontinuation rates compared to the control group. This meta-analysis suggests that metformin shows potential as a treatment for antipsychotic-induced hyperprolactinemia, with a favorable tolerability profile in patients with schizophrenia, particularly at higher doses, shorter treatment durations, higher BMI, and longer illness duration. Despite the robustness of the findings, high heterogeneity necessitates cautious interpretation. Future research should explore demographic and clinical factors influencing the response to metformin for optimizing treatment.